Sense-antisense gene pairs: sequence, transcription, and structure are not conserved between human and mouse - Wood, Emily J.; Chin-Inmanu, Kwanrutai; Jia, Hui; Lipovich, Leonard (Frontiers in Genetics, 2013)
Previous efforts to characterize conservation between the human and mouse genomes focused largely on sequence comparisons. These studies are inherently limited because they don’t account for gene structure differences, which may exist despite genomic sequence conservation. Recent high-throughput transcriptome studies have revealed widespread and extensive overlaps between genes, and transcripts, encoded on both strands of the genomic sequence. This overlapping gene organization, which produces sense-antisense gene pairs, is capable of effecting regulatory cascades through established mechanisms. We present an evolutionary conservation assessment of sense-antisense pairs, on three levels: genomic, transcriptomic, and structural. From a genome-wide dataset of human sense-antisense pairs, we first identified orthologous loci in the mouse genome, then assessed their transcription in the mouse, and finally compared the genomic structures of sense-antisense pairs expressed in both species. We found that approximately half of human sense-antisense loci have single orthologous locations in the mouse genome; however, only half of those orthologous locations have sense-antisense transcriptional activity in the mouse. This suggests that high human-mouse gene conservation overlooks widespread distinctions in sense-antisense pair incidence and expression. We compared gene structures at orthologous sense-antisense loci, finding frequent differences in gene structure between human and orthologous mouse sense-antisense pair members. Our categorization of human sense-antisense pairs with respect to mouse conservation of expression as well as structure points to limitations of mouse models. Gene structure differences, including at sense-antisense loci, may account for some of the phenotypic distinctions between primates and rodents. Genes in non-conserved sense-antisense pairs may contribute to evolutionary lineage-specific regulatory outcomes.